Boundary behaviour of open, light mappings in metric measure spaces - Cristea, Mihai (Annales Fennici Mathematici, 2021)
We study the boundary behaviour of open, light mappings satisfying generalized modular inequalities in general metric measure spaces. We extend in this way known facts from the theory of quasiregular mappings and from their recent generalizations, namely the mappings of finite distortion and the so called ring mappings.